APLIKASI PENENTUAN MINAT STUDI SISWA MENGGUNAKAN METODE SINGLE LINKAGE CLUSTERING (STUDI KASUS : SMK NEGERI 1 KENDARI) - Nurfinasari Nurfinasari; Sutardi Sutardi; Mutmainnah Muchtar (semanTIK, 2018)
The process of determining the areas of interest (specialization) in Vocational Schools in Indonesia is organized to match the ability and interests of learners to the field of their choosing. SMK Negeri 1 Kendari is one of the institutions engaged in the field of education, especially vocational which stood under the auspices of Education Department of Kendari City and is located at Jl. Jend. A. Yani No. 17 Kota Kendari. This school has 4 majors that can be selected by students, among others: Accounting, Office Administration, Trade, Computer Engineering and Network (TKJ). The process of determining the program of expertise SMK Negeri 1 Kendari still using the manual way, if done by manual it will require extra precision because the data is quite a lot and has many weaknesses that allow errors in the process of majors. Therefore, proper classification of majors is required, one of them using technology in the field of data mining. In this research, single linkage clustering method is chosen, which is where the distance between clusters will get shorter time between clusters to achieve the final result and as media optimization in terms of facilitating the school in determining the majors of interest students. From the results of research and implementation note that the system can classify the data of student interest in SMKN 1 Kendari by using Single Linkage Clustering, Make it easier to clustering data by calculating the closest distance of each cluster object and student interest in SMKN 1 Kendari shows that 35.7 % Accounting and Finance, 28.6% Business and Marketing, 28.6% Office Management and 7.1% Computer & Network Engineering, from 438 student data.Keywords—Data Mining, Single Linkage Clustering, Interest in Studies DOI : 10.5281/zenodo.1402386